Thromboembolic events with recombinant activated factor VII in spontaneous intracerebral hemorrhage: results from the factor seven for acute hemorrhagic stroke (FAST) trial - Diringer, Michael N.; Skolnick, Brett E.; Mayer, Stephan A.; Steiner, Thorsten; Davis, Stephen M.; Brun, Nikolai C.; Broderick, Joseph P. (Stroke, 2010)
Background and Purpose: Patients with intracerebral hemorrhage have a high risk of thromboembolic events (TEs) due to advanced age, hypertension, atherosclerosis, diabetes, and immobility. Use of recombinant activated factor VII (rFVIIa) could increase TEs in high-risk patients. Factor Seven for Acute Hemorrhagic Stroke (FAST) trial data were reviewed to define the frequency of and risk factors for TE with rFVIIa. - Methods: Eight hundred forty-one patients presenting <3 hours after spontaneous intracerebral hemorrhage were randomized to 20 or 80 μg/kg of rFVIIa or placebo. Those with Glasgow Coma Scale score <5, planned early surgery, coagulopathy, or recent TE were excluded. Myocardial, cerebral, or venous TEs were subject to detailed reporting and expedited local review. Additionally, a blinded Data Monitoring Committee reviewed all electrocardiograms, centrally analyzed troponin I values, and CT scans. - Results: There were 178 arterial and 47 venous TEs. Venous events were similar across groups. There were 49 (27%) arterial events in the placebo group, 47 (26%) in the 20-μg/kg group, and 82 (46%) in the 80 μg/kg group (P=0.04). Of the myocardial events, 38 were investigator-reported and 103 identified by the Data Monitoring Committee. They occurred in 17 (6.3%) placebo and 57 (9.9%) rFVIIa patients (P=0.09). Arterial TEs were associated with: receiving 80 μg/kg rFVIIa (OR=2.14; P=0.031), signs of cardiac or cerebral ischemia at presentation (OR=4.19; P=0.010), age (OR=1.14/5 years; P=0.0123), and prior use of antiplatelet agents (OR=1.83; P=0.035). Ischemic strokes possibly related to study drug occurred in 7, 5, and 8 patients in the placebo, 20 μg/kg, and 80-μg/kg groups, respectively. - Conclusions: Higher doses of rFVIIa in a high-risk population are associated with a small increased risk of what are usually minor cardiac events. Demonstration of the ability of rFVIIa to improve outcome in future studies should be driven by its effectiveness in slowing bleeding outweighting the risk of a small increase in arterial TEs.
Published online: December 3, 2009
Gesehen am 06.02.2023